Un paese senza avvocati? Stereotipi, fraintendimenti e riflessioni storico-comparative sulla professione legale in Giappone - Giorgio Fabio Colombo (Lingue Culture Mediazioni, 2017)
Japan is often depicted as a country ‘without lawyers’. This would of course be a product of the legendary Japanese ‘weak legal consciousness’. From transactions based on personal relationships rather than contracts, to the legendary preference for conciliation rather than litigation, according to the cliché it seems that in Japan there is little room for law – and lawyers. Japan is indeed the industrialized country with fewer lawyers-per-capita. The Japanese legal profession, however, has recently gone through a major reorganization process: in 2006 it implemented a system broadly based on the U.S. Law School, with the specific purpose of having ‘more lawyers’. After ten years, the reform failed to accomplish its purpose: while the number of lawyers indeed increased, no significant benefits for the system as a whole may be seen. Moreover, the idea that now there are ‘too many lawyers’ has become more and more popular. How is it possible, then, that lawyers are not enough and too many at the same time? By using a historical and comparative approach, this paper intends to explore the Japanese legal profession(s), with a special focus to challenge the well-worn stereotype of ‘a country without lawyers’.